2010
DOI: 10.1152/ajpheart.00592.2009
|View full text |Cite
|
Sign up to set email alerts
|

NFATc4 is negatively regulated in miR-133a-mediated cardiomyocyte hypertrophic repression

Abstract: Activation of NFAT (nuclear factor of activated T cells)-mediated hypertrophic signaling is a major regulatory response to hypertrophic stimuli. A recent study unveiled potential regulatory roles for microRNA-133a (miR-133a) in cardiac hypertrophy. To date, however, no connection has been made between miR-133a and NFAT signaling. In this study, we determined that NFATc4, a hypertrophy-associated mediator, is negatively regulated by miR-133a. Two conserved base-pairing sites between the NFATc4 3'-untranslated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 47 publications
2
67
0
Order By: Relevance
“…miR-9 directly targets myocardin and interferes with the nuclear activity of NFAT (69). miR-133a inhibits hypertrophy by direct targeting of calcineurin (68), NFAT (66), and Cdc42 and RhoA (63), miR-1 targets twinfilin-1 (70), and calmodulinmediated hypertrophic signaling (64,71). Genetic deficiency of miR-133a results in extensive fibrosis, impaired cardiac function, and pathological remodeling (72).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-9 directly targets myocardin and interferes with the nuclear activity of NFAT (69). miR-133a inhibits hypertrophy by direct targeting of calcineurin (68), NFAT (66), and Cdc42 and RhoA (63), miR-1 targets twinfilin-1 (70), and calmodulinmediated hypertrophic signaling (64,71). Genetic deficiency of miR-133a results in extensive fibrosis, impaired cardiac function, and pathological remodeling (72).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of these miRNAs enhances hypertrophic growth and their inhibition confers resistance to cardiac stress (51, 54 -61). Among the anti-hypertrophic miRNAs, miR-98/let-7 regulates cardiac hypertrophy indirectly via thioredoxin (62), the other three miRNAs (miR-9, miR-1, and miR-133) could directly inhibit response of cardiomyocytes to hypertrophic stimuli (53,(63)(64)(65)(66)(67)(68)(69). Expression of these three miRNAs is down-regulated by hypertrophy agonists and their overexpression diminished the hypertrophic response.…”
Section: Microrna-378 Targets Ras Signaling In Cardiac Myocytesmentioning
confidence: 99%
“…Although accumulating data have suggested that miRNAs function in regulating SMC proliferation and differentiation (23)(24)(25), whether this effect is achieved by regulating NFAT signaling pathway through miRNAs is still unclear. In this study, we performed a high throughput screening by using an in-house-made miRNA expression library and NFAT luciferase reporter system.…”
Section: Abnormal Proliferation and Phenotypic Modulation Of Pulmonarmentioning
confidence: 99%
“…Interestingly, miR-214 was reported to target and repress NCX1 and protects cardiomyocytes from Ca 2+ -induced cell death during ischemia/reperfusion injury. 177 In addition, miR-133a, which is bi-cistronically clustered with miR-1, was shown to have a strong effect on Ca 2+ signaling pathways in cardiomyocytes by targeting calcineurin, 178 NFATc4, 179 and IP 3 R2. 180 The latter study also showed that IP 3 -induced Ca 2+ release significantly contributes, in a feed-forward mechanism, to the down-regulation of miR-133a during hypertrophy and accentuation of pathological remodeling.…”
Section: Microrna-mediated Ca 2+ Signals and Cardiac Hypertrophymentioning
confidence: 99%